Caracterização de compósitos (WPC) produzidos com termoplásticos, madeira e bagaço de uva - Berger, Camila (2017)
The use of lignocellulosic wastes in the manufacture of polymer composites has as main advantages the low acquisition cost, interesting resistance / weight ratio and low environmental impact, wich generating more ecological composites. Thus the aim of this study was to incorporate the grape pomace residue and pinus particles from the sawmill waste, to make as well as wood-plastic composites (WPC) with and without the incorporation of grape pomace,and composites with just grape pomace using polypropylene (PP) and high density polyethylene (HDPE) as matrix. With the purpose of adding value and promoting the sustainability of the productive chain of wine and grape juice. Six different compositions were manufactured, three characterizing the PP composites and the other three being the HDPE composites. The proportion of each polymer was set at 50% in the composite for both matrices, varying the particles of pinus and grape pomace. They were physically characterized by MEV (scanning electron microscopy), TG (thermogravimetric analysis), DSC (differential scanning calorimetry), DMA (dynamic-mechanical analysis) besides density, moisture content, water absorption and swelling thickness and mechanical properties as flexural modulos and flexural strength, tensile strength and Shore D hardness.The results showed that WPCs made with just pinus particle and with mixture of both lignocellulosic materials of both matrices presented better mechanical performance than the composites with only grape pomace. These, on the other hand, presented better dimensional stability and less water absorbed than composites with only pinus particles. This makes the use of this residue an interesting and sustainable alternative in the production of polymeric composites.Both lignocellulosic materials did not present as nucleating agents.